Meningkatkan Minat dan Hasil Belajar Bahasa Indonesia melaui Penerapan Belajar Kelompok Siswa Kelas IX.A SMP Negeri 17 Mataram - Andayani, Sri Astuti (YASIN, 2022)
The goal to be achieved from this research is to find out Increasing Interest and Learning Outcomes of Indonesian Language through the Application of Study Groups for Class IX.A Students of SMP Negeri 17 Mataram in the Academic Year 2022/2023. This research is a classroom action research. The subjects in this study were 32 students of class IX.A SMP Negeri 17 Mataram with 20 male students and 14 female students. Data collection techniques used are observation, documentation, and tests. Observations are used to collect data on learning interest. The test is used to measure learning achievement in Indonesian subjects. Data analysis used is descriptive qualitative and descriptive quantitative. The increase in students' cognitive learning outcomes before and after the implementation of group learning at SMP Negeri 17 Mataram can be seen from the percentage gain of each indicator, namely: The average value of the initial data students obtained 74.10% increased to 77.69 in cycle I and obtained 82.84 in cycle II. While students who completed the data were 17 people then obtained 25 in cycle I and experienced an increase to 30 people in cycle II with each classical completeness obtained initial data from 64.10 to 78.13 in cycle I and increased to 193.75 in cycle II, this shows that all the indicators expected by the researcher on the reading ability of grade I students were successfully achieved. Lesson planning carried out by the teacher increased from 75.00% in cycle I and 85.00% in cycle II. So the lesson planning carried out by the teacher is very good. While the implementation of learning carried out by the teacher also experienced an increase from 79.17% in cycle I to 87.50% in cycle II. So the implementation of learning carried out by the teacher has also increased. Student learning activities that the average percentage in the first cycle is 80.00%. But in cycle II, student learning activities increased to 90.00%. So student learning activities in learning Indonesian are very good.